THE EFFECTIVENESS OF THE 'KEMBANG RANDU' WEBSITE IN SUPPORTING PUBLIC SERVICE TRANSFORMATION IN RANDUPITU VILLAGE, PASURUAN REGENCY - Nuzulla, Mei Firdaus; Agustina, Isna Fitria (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The research aims to analyze how digitalization through the